Analysis of Factor Affecting Work Stress for Employees in Pamekasan Nursing Academy - Kuzzairi Kuzzairi; Byba Melda Suhita (Master of Public Health Program Institut Ilmu Kesehatan STRADA Indonesia, 2018)
Each workplace always feeds on the potential hazards that may affect the health of the workforce or may cause work-related illness. Psychic disorder is a potential hazard that is often overlooked when the potential of this psychic hazard is also an important factor that needs to be considered in relation to the mental health of workers. Factors that are suspected to be stressors of work stress are the personality, workload, organizational structure and climate, career development and work environment. The purpose of this study is to analyze the factors that affect the work stress of employees Akper Pemkab Pamekasan. The type of this research is quantitative research with analytic observational research design with cross sectional approach. The study was conducted on 12 to 23 February 2018 at Akper Pemkab Pamekasan with a population of 42 employees. The sample size is 38 respondents. The independent variables are personality, workload, organizational structure and climate, career development and work environment. Variable dependent is work stress of Akper employees Pamekasan regency. data were collected using questionnaires. Data were analyzed using logistic regression test with α = 0,05. The results showed that variable X1 (personality) with p = 0,639; OR = 13,749, Variable X4 (career development) with p = 0,028; OR = 15.270, variable X5 (working environment) with p = 0.999; OR = 1,460. So it can be concluded that the dominant factor and influence work stress employees Akper Pemkab Pamekasan is career development factor with the influence of 15.270. Employee career development that does not satisfy the cause of work stress so it is necessary to provide information and communication in a transparent and accountable about the mechanism of career development level in accordance with the performance.